Self-awareness predicts fitness to drive among adults referred to occupational therapy evaluation - Rosenfeld, Meirav; Goverover, Yael; Weiss, Penina (Frontiers in Rehabilitation Sciences, 2022)
Background: Driving is associated with independence, well-being, quality of life, and an active lifestyle. Driving requires cognitive, motor, and visual skills, including self-awareness and processing speed. This study examines whether driver self-awareness, motor processing speed, and cognitive processing speed can predict fitness to drive among individuals referred to occupational therapy evaluation due to concerns about their driving ability. Method: In this cross-sectional study, 39 participants were referred to off- and on-road driving evaluation to determine their fitness to drive due to changes in health status, advanced age, license renewal requirement, or prior automobile accidents. A registered occupational therapist (OT) classified 23 of the participants as fit to drive and 16 as unfit to drive. Motor and cognitive processing speed were assessed by the Stationary Perception-Reaction Timer and the Color Trails Test, respectively. Driving self-awareness was assessed by comparing the DI and OT evaluations to the participants’ estimation of their own on-road driving performance. Results: The fit-to-drive participants had a better motor and cognitive processing speed than those unfit-to-drive. The unfit-to-drive group overestimated their driving ability, whereas the fit-to-drive group accurately or almost accurately estimated their driving ability. Driving self-awareness was a significant predictor of participants’ fitness to drive. Conclusions: This study demonstrates the importance of self-awareness for predicting fitness to drive among people at risk for compromised driving skills. Thus, driving self-awareness should be addressed as part of fitness-to-drive evaluations and interventions.